2010
DOI: 10.1007/s12223-010-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring prebiotic oligosaccharides in poultry feed mixtures

Abstract: The presence of raffinose series oligosaccharides (RSO) was determined by an enzymic method in three commercially available chicken feed mixtures. All feed mixtures contained RSO at a concentration of 2.1-2.2%. Soya meal was identified as the exclusive source of RSO. Subsequently, the bifidogenic effect of stachyose (main soya bean RSO) was also assigned on the growth of poultry intestinal bifidobacteria. Bifidobacteria were counted in chicken intestinal tract using cultivation and FISH methods. Four out of 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Hence, there are efforts focused on reducing the RFO content in crop seeds (Dierking and Bilyeu, 2008;Yang et al, 2015). By contrast, RFOs are an important energy resource for beneficial microflora in the small intestine (Rada et al, 2008;Grmanova et al, 2010). Understanding the metabolic pathway of RFOs and their physiological function would assist researchers to manipulate RFOs in crop plants for fulfilling these multifarious goals.…”
Section: Regulation Of Plant Seed Vigor Through Manipulation Of Rfosmentioning
confidence: 99%
“…Hence, there are efforts focused on reducing the RFO content in crop seeds (Dierking and Bilyeu, 2008;Yang et al, 2015). By contrast, RFOs are an important energy resource for beneficial microflora in the small intestine (Rada et al, 2008;Grmanova et al, 2010). Understanding the metabolic pathway of RFOs and their physiological function would assist researchers to manipulate RFOs in crop plants for fulfilling these multifarious goals.…”
Section: Regulation Of Plant Seed Vigor Through Manipulation Of Rfosmentioning
confidence: 99%
“…Previous studies show that soybean holds high content of the stachyose, and it was identified as the exclusive source of stachyose (Grmanová et al 2010). However, through our designed protocal, stachyose could be extracted from yinmiao, and the yield of stachyose is 46.99% by RSM.…”
Section: Resultsmentioning
confidence: 88%
“…However, stachyose is proved to be a prebiotics (Gibson and Roberfroid 1995;Seo et al 2007;Rabelo et al 2009), which can stimulate the growth of bifidobacteria in the human and animal intestine and protect the function of organs by eliminating harmful substances (Grmanová et al 2010;Rada et al 2002 andLiying et al 2003). It is also regarded as a potential substitute for sugar in diabetes patients (Yin et al 2006;Zhang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, not all studies report unequivocal positive results of in-feed prebiotics, even under stress conditions such as Eimeria challenge (Faber et al, 2012). Grmanova et al (2010) stated that chicken feed mixtures naturally contain prebiotic oligosaccharides in the form of RFOs in higher concentrations than what is commonly recommended as artificial supplementation. Thus, inconsistency of results obtained in different trials with different prebiotic supplements may depend on the combination of other ingredients in the feed formula.…”
Section: Probioticsmentioning
confidence: 99%